2016
DOI: 10.1371/journal.pmed.1002098
|View full text |Cite|
|
Sign up to set email alerts
|

Supported Telemonitoring and Glycemic Control in People with Type 2 Diabetes: The Telescot Diabetes Pragmatic Multicenter Randomized Controlled Trial

Abstract: BackgroundSelf-monitoring of blood glucose among people with type 2 diabetes not treated with insulin does not appear to be effective in improving glycemic control. We investigated whether health professional review of telemetrically transmitted self-monitored glucose results in improved glycemic control in people with poorly controlled type 2 diabetes.Methods and FindingsWe performed a randomized, parallel, investigator-blind controlled trial with centralized randomization in family practices in four regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(136 citation statements)
references
References 26 publications
6
127
1
2
Order By: Relevance
“…This review verified that five studies follow-up the program by using a face-to-face follow-up (12,15,17,(22)(23)(24)33) . Three studies were noticed to follow-up the program by using the telephone method (13,14,25,26,32) .…”
Section: Follow-up Strategiessupporting
confidence: 64%
See 4 more Smart Citations
“…This review verified that five studies follow-up the program by using a face-to-face follow-up (12,15,17,(22)(23)(24)33) . Three studies were noticed to follow-up the program by using the telephone method (13,14,25,26,32) .…”
Section: Follow-up Strategiessupporting
confidence: 64%
“…We found that DSME based individual program was conducted into 40.9% of the studies (12,13,16,20,23,25,29,30,32) and 59.1% of the studies offered the DSME in a combination of individual and group education (12,14,15,17,20,21,27,31,32,34) . In general, The individual or group-based program provided the intervention of several strategies, including personalized counseling, feedback regarding goal-setting and problem-solving, support for self-care practice from family members, and the follow-up session.…”
Section: Diabetes Mellitus Self-management Education (Dsme)mentioning
confidence: 99%
See 3 more Smart Citations